Is the American Model Miss World? Choosing between the Anglo-Saxon Model and a European-Style Alternative - Henri L.F. de Groot; Richard Nahuis; Paul J.G. Tang (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
In Lisbon, the European Union has set itself the goal to become the most competitive economy in the world in 2010 without harming social cohesion and the environment. The motivation for introducing this target is the substantially higher GDP per capita of US citizens. The difference in income is mainly a difference in the number of hours worked per employee. In terms of productivity per hour and employment per inhabitant, several European countries score equally well or even better than the United States, while at the same time they outperform the United States with a more equal distribution of income. The European social models are at least as interesting as the US model that is often considered a role model.In an empirical analysis for OECD countries, we aim to unravel 'the secret of success'. Our regression results show that income redistribution (through a social security system) does not necessarily lead to lower participation and higher unemployment, provided that countries supplement it with active labour market policies. Especially, spending on employment services like job-search assistance and vocational guidance, seems effective. Furthermore, the results suggest that generous unemployment benefits of short duration contribute to employment without widening the income distribution.
Keywords: 330; welfare states; income inequality; unemployment; productivity; participation; labour market policies